The Impact merger and acquisition on publicly listed targets' shareholder wealth: Evidence from UK. - FU, LEI (2014)
This paper mainly studies how public target M&A impacts on the wealth of shareholder around the announcement date in short run. The result shows that acquirers will obtain significantly negative abnormal return around the announcement date.Also, because different lengths of event window will capture different significant effects of merger and acquisition, this research chooses three different event windows and compare theirresults. Through this comparison, it could conclude that the shorter event window could better capture the significant effect of merger and acquisition. In addition, since the payment method of bidders as well as the different characteristics of acquirers and targets may result in variation in acquires' return, this paper selects and examines five factors which may impact on the abnormal return, including firm size, relative size, payment method, diversification and Tobin's Q. Importantly, the final result indicates that the cash offer acquirers obtain 4.53% points higher abnormal return than the stock offerbidders. The abnormal return of acquirers are positive related to the firm size of acquirers, whereas are negative related to the Tobin's Q of the targets. Finally, the result shows that five factors: relative size and diversification will not significantly impact on the abnormal return of acquirers in the short term.